2019
DOI: 10.35188/unu-wider/2019/697-5
|View full text |Cite
|
Sign up to set email alerts
|

Dancing with dragons: Chinese import penetration and the performances of manufacturing firms in South Africa

Abstract: provides economic analysis and policy advice with the aim of promoting sustainable and equitable development. The Institute began operations in 1985 in Helsinki, Finland, as the first research and training centre of the United Nations University. Today it is a unique blend of think tank, research institute, and UN agency providing a range of services from policy advice to governments as well as freely available original research.The Institute is funded through income from an endowment fund with additional cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…This may be both through intrafirm channels (firms become leaner or downsize) and through composition e↵ects at the firm level (more labor-intensive and less productive firms being more likely to close) and at the sector level (more labour intensive sectors of manufacturing being more heavily a↵ected) in the face of import penetration from Chinese manufactures. Our result is in accordance with that of Busse et al (2016), Torreggiani and Andreoni (2019), Edwards et al (2020) and Edwards and Jenkins (2015). The latter found that in the case of South Africa import penetration from China caused "manufacturing output to be 5 per cent lower in 2010 than it otherwise would have been.…”
Section: Regression Resultssupporting
confidence: 91%
“…This may be both through intrafirm channels (firms become leaner or downsize) and through composition e↵ects at the firm level (more labor-intensive and less productive firms being more likely to close) and at the sector level (more labour intensive sectors of manufacturing being more heavily a↵ected) in the face of import penetration from Chinese manufactures. Our result is in accordance with that of Busse et al (2016), Torreggiani and Andreoni (2019), Edwards et al (2020) and Edwards and Jenkins (2015). The latter found that in the case of South Africa import penetration from China caused "manufacturing output to be 5 per cent lower in 2010 than it otherwise would have been.…”
Section: Regression Resultssupporting
confidence: 91%
“…Import penetration, especially from China, has also increasingly shifted from low-to medium-tech products. This has crowded out several South African companies, especially those that were not investing in developing their capabilities (Torreggiani and Andreoni, 2019).…”
Section: Global Value-chain Integration: Challenges For Upgradingmentioning
confidence: 99%
“…This means that while the middle-income countries in the SEA group have already started integrating into GVCs, South Africa has been slow in linking up into GVCs, similarly to a number of countries in Latin America. In addition, the 'out' phase has not materialized either, as the country's dependence on international trade increased after the end of apartheid in 1994, with China becoming its main trade partner in 2008 (Torreggiani and Andreoni, 2019). On the one hand, the country has relied increasingly on imports of final goods to satisfy its domestic demand; on the other hand, it has served as a gateway and export platform for foreign investors and traders to access the rest of the African continent.…”
Section: Factors Contributing To the Successes In South Korea And Chinamentioning
confidence: 99%
“…They also differ from the industrial strategies of east Asian newly industrialized countries (NICs), with their emphasis on building domestic productive capabilities through rents fostering strategic value chain integration, first through import substitution (building NVCs) and then by export promotion (insertion into RVCs and GVCs) (Chang 1994;Andreoni 2019). Among industrial policy scholars, there remains a bias against NVCs, with the assumption that exposure to global competition through exporting is necessary to induce 'learning for productivity' (Whitfield et al 2015), despite the high levels of import competition in the liberalized domestic markets of many countries in the global South (e.g., Torreggiani and Andreoni 2019).…”
Section: Literature Reviewmentioning
confidence: 99%